2002
DOI: 10.1108/14691930210435624
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of intellectual capital measurement from Asia, Europe and the Middle East

Abstract: The purpose of this empirical study is to investigate the current state of best practices in the trans‐disciplinary field of intellectual capital (IC) management and measurement. First, this paper is intended to provide a conceptual framework for IC analysis. Second, it explores interesting factors regarding the dynamics of measuring and reporting IC in pioneer firms in Asia, Europe and the Middle East. After an in‐depth case analysis of leading firms in this field, a holistic IC model is discussed, which invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(64 citation statements)
references
References 18 publications
0
58
0
6
Order By: Relevance
“…Elements of intellectual capital differ between different parts of the existing literature and research. This study summarized a stream of literature and concluded that the focuses have been as follows: human capital, organizational capital, customer capital, structural capital, individual capital, collective capital, relational capital, innovation capital, and strategic alliances (Allee, 1999;Bontis et al, 2000;Brooking, 1996;Canibano, Garcia-Ayuso, & Sanchez, 2000;Carson, Ranzjin, Winefield, & Marsdon, 2004;Cascio, 1998;Chen & Lin, 2004;Davenport & Prusak, 1998;Edvinsson & Malone, 1997;Fischer, 2001;Haanes & Lowendahl, 1997;Kaplan & Norton, 1996;MERITUM, 2001;Mouritsen, Larsden, & Bukh, 2001;Nahapiet & Ghoshal, 1998;Ordonez de Pablos, 2002Petrash, 1996;Sanchez, Chaminad, & Olea, 2000;Stewart, 1997;Sveiby, 1997;Youndt, Subramaniam, & Snell, 2004). Nevertheless, recent research has validated that each of the forms of capital will be influenced by the newest kind of capital, called innovation capital, in a drastically changing world such as the one that we inhabit today (Zeng, 2002;Zeng & Gu, 2003).…”
Section: Intellectual Capitalmentioning
confidence: 98%
“…Elements of intellectual capital differ between different parts of the existing literature and research. This study summarized a stream of literature and concluded that the focuses have been as follows: human capital, organizational capital, customer capital, structural capital, individual capital, collective capital, relational capital, innovation capital, and strategic alliances (Allee, 1999;Bontis et al, 2000;Brooking, 1996;Canibano, Garcia-Ayuso, & Sanchez, 2000;Carson, Ranzjin, Winefield, & Marsdon, 2004;Cascio, 1998;Chen & Lin, 2004;Davenport & Prusak, 1998;Edvinsson & Malone, 1997;Fischer, 2001;Haanes & Lowendahl, 1997;Kaplan & Norton, 1996;MERITUM, 2001;Mouritsen, Larsden, & Bukh, 2001;Nahapiet & Ghoshal, 1998;Ordonez de Pablos, 2002Petrash, 1996;Sanchez, Chaminad, & Olea, 2000;Stewart, 1997;Sveiby, 1997;Youndt, Subramaniam, & Snell, 2004). Nevertheless, recent research has validated that each of the forms of capital will be influenced by the newest kind of capital, called innovation capital, in a drastically changing world such as the one that we inhabit today (Zeng, 2002;Zeng & Gu, 2003).…”
Section: Intellectual Capitalmentioning
confidence: 98%
“…From a traditional viewpoint, the main purpose of managers is to focus on earning maximization. More recently, however, scholars tend to believe that managers need to pay more attention to internal knowledge accumulation and development in their organizations (Edvinsson, 1997;Bontis, 2001;Ordonez de Pablos, 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Both the CIMA and CICA, leading accounting bodies, have supported the IC disclosure initiatives of their [54,55], etc. Based on best practices observed in more than 100 European Union corporations, the Meritum projects have resulted in "guidelines" on how to report IC.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%